2017
DOI: 10.1136/bmjopen-2017-016491
|View full text |Cite
|
Sign up to set email alerts
|

The realities of partnership in person-centred care: a qualitative interview study with patients and professionals

Abstract: ObjectiveAlthough conceptual definitions of person-centred care (PCC) vary, most models value the involvement of patients through patient-professional partnerships. While this may increase patients’ sense of responsibility and control, research is needed to further understand how this partnership is created and perceived. This study aims to explore the realities of partnership as perceived by patients and health professionals in everyday PCC practice.DesignQualitative study employing a thematic analysis of sem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
130
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(133 citation statements)
references
References 40 publications
3
130
0
Order By: Relevance
“…Other RCTs of gPCC have shown decreased re-hospitalisation and increased HRQoL [12], increased use of target doses of life-prolonging medication [25] and a significant cost reduction in patients with severe chronic heart failure [26]. gPCC emphasizes the patient's own resources which helps identifying reasonable goals during recovery [27], and facilitates both formal and informal partnership which patients perceive as a sense of ease and security [28]. From the perspective of health care professionals, gPCC introduces a new practice by facilitating active patient participation in decisions about their care, as well as creating a more person-centred approach toward improved inter-professional teamwork [29].…”
Section: Discussionmentioning
confidence: 99%
“…Other RCTs of gPCC have shown decreased re-hospitalisation and increased HRQoL [12], increased use of target doses of life-prolonging medication [25] and a significant cost reduction in patients with severe chronic heart failure [26]. gPCC emphasizes the patient's own resources which helps identifying reasonable goals during recovery [27], and facilitates both formal and informal partnership which patients perceive as a sense of ease and security [28]. From the perspective of health care professionals, gPCC introduces a new practice by facilitating active patient participation in decisions about their care, as well as creating a more person-centred approach toward improved inter-professional teamwork [29].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Chevakasemsook et al [25] highlights that restrictions within medical records cause problems due to documentation of care plans with a humanistic perspective. Moreover, research [1,2,26] has shown that listening to patients facilitates joint agreement, which shortens the hospital stay and reduces costs by maintain continuity and partnership across professional boundaries. However, mutual care plans are described as tool of professional caregivers, not the patients.…”
Section: Introductionmentioning
confidence: 99%
“…In line with the literature (103) , the results in this thesis show that by providing the right conditions for communication and mutual cooperation, a partnership can be created (II). The literature supports this finding and informal elements, such as emotionally supportive relationships, are important for ultimately determining the level of shared decision-making, paving the way for patients participations in care decisions (104,117).…”
Section: Being Met With Trust and Respectmentioning
confidence: 67%
“…Shared decision-making may be defined as the process of interaction with patients who wish to be involved in making decisions. The concept of shared decision-making entails that HC professionals have the responsibility to inform and recommend treatment to patients, but the process of deciding on how to act is shared (117). The goal is to enhance patient involvement and, on the basis of the available evidence, facilitate 'evidence-based patient choice'.…”
Section: Being Met With Trust and Respectmentioning
confidence: 99%
See 1 more Smart Citation